2021
DOI: 10.1001/jamanetworkopen.2021.37250
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Children With Life-Threatening Conditions and Their Parents’ and Siblings’ Mental and Physical Health

Abstract: IMPORTANCE Despite concerns regarding the potential deleterious physical and mental health outcomes among family members of a child with a life-threatening condition (LTC), few studies have examined empirical measures of health outcomes among these family members.OBJECTIVES To examine whether mothers, fathers, sisters, and brothers of children with 1 of 4 types of pediatric LTCs have higher rates of health care encounters, diagnoses, and prescriptions compared with families of children without these conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 50 publications
3
33
0
1
Order By: Relevance
“…Previous studies found a higher risk of worse mental health among parents of children with cancer compared with the general population, 7 , 14 , 30 , 31 which was also observed in our study. We found that fathers were affected immediately when their child was diagnosed with cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies found a higher risk of worse mental health among parents of children with cancer compared with the general population, 7 , 14 , 30 , 31 which was also observed in our study. We found that fathers were affected immediately when their child was diagnosed with cancer.…”
Section: Discussionsupporting
confidence: 90%
“…A study using the insurance claims data of US families suggested a 66% increase in the risk of mental health diagnoses in fathers with two years of follow-up. 30 In a Danish registry-based study, however, elevated risk of hospital contacts for psychiatric disorders was not observed. 18 The differences in findings may be explained by the different sampling strategies and potential underestimation of mental health disorders.…”
Section: Discussionmentioning
confidence: 93%
“…These may take the form of in-person events, group offerings, virtual live meeting rooms, or asynchronous communication forums such as social media or chat rooms [ 57 ]. Despite the accessibility of virtual social support options, parent caregivers may experience significant behavioral health challenges that can be exacerbated by caregiving demands and all that comes with caring for RD [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parents provide the majority of care [ 6 ], although siblings also play important roles [ 16 , 49 ]. While the family impacts the child’s care, a child’s illness also impacts the physical and mental health and well-being of family members [ 50 , 51 , 52 , 53 , 54 ]. Negative impacts can be mitigated by extended family and close friends [ 55 ], who can provide emotional support and help with tasks such as cooking, cleaning, and childcare [ 56 , 57 ].…”
Section: Conceptual Framework Of Home-based Care For Children With Se...mentioning
confidence: 99%